A prospective phase II randomized study of deferasirox to prevent iatrogenic iron overload in patients undertaking induction/consolidation chemotherapy for acute myeloid leukaemia. (17th April 2013) - Kennedy, Glen A.; Morris, Kirk L.; Subramonpillai, Elango; Curley, Cameron; Butler, Jason; Durrant, Simon
Summary This prospective randomized phase II study aimed to determine the safety and efficacy of deferasirox in preventing iatrogenic iron overload in patients receiving induction/consolidation chemotherapy for acute myeloid leukaemia (AML) ize. Serum ferritin, transferrin saturation and CRP were measured pre‐, mid‐ and post‐ each chemotherapy cycle. Patients were randomized to receive either therapy with deferasirox vs. no deferasirox therapy once serum ferritin increased to >500 μg/l. The trial was stopped prematurely due to excess gastrointestinal (GI) and infectious toxicity demonstrable in the deferasirox arm, after 10 patients had been randomized to deferasirox and 6 patients to the control arm. Overall, deferasirox was poorly tolerated, with median maximum tolerated dose only 13·8 mg/kg/d and no patient able to tolerate doses >20 mg/kg/d. Median duration of deferasirox therapy was only 72 d (range 19–130 d), with 9/10 patients requiring unplanned dose interruptions and 4/10 patients unable to continue the drug predominantly due to GI effects. Although all 3 treatment‐related deaths occurred in the deferasirox arm (P = 0·25), median overall survival was similar between treatment arms. Use of deferasirox to prevent iatrogenic iron overload in AML patients undertaking induction/consolidation is poorly tolerated and appears to be associated with excess GI and infectious toxicity.